Artificial Larval Diet Mediates the Microbiome of Queensland Fruit Fly - Majumder, Rajib; Sutcliffe, Brodie; Adnan, Saleh Mohammad; Mainali, Bishwo; Dominiak, Bernard C.; Taylor, Phillip W.; Chapman, Toni A. (Frontiers in Microbiology, 2020)
Larval diets used for artificial rearing can have a significant effect on insect biology. The Queensland fruit fly (aka ‘Qfly’), Bactrocera tryoni (Froggatt) (Diptera: Tephritidae), is one of the greatest challenges for fruit growers in Australia. The sterile insect technique (SIT) is being developed to manage outbreaks in regions that remain free of Qfly and to reduce populations in regions where this species is endemic. Factory scale rearing is essential for SIT; however, artificial larval diets are known to affect the microbiome of Qfly, which may then affect fly performance. In this study, high-throughput Illumina sequencing was used to assess the Qfly microbiome in colonies reared, for five generations from nature, on two common artificial diets (carrot and gel). At generation five (G5), the microbiome was assessed in larvae, pupae, adult males and adult females and standard fly quality control parameters were assessed together with additional performance measures of mating propensity and survival under nutritional stress. At the genus level, bacterial communities were significantly different between the colonies reared on the two larval diets. However, communities converged at Phyla to family taxonomic levels. Interestingly, pathogenic bacterial genera (e.g., Morganella, Citrobacter, Providencia, Burkholderia) were highly abundant in all developmental stages of Qfly reared on the gel diet, when compared to the carrot diet. Despite abundance of these commonly pathogenic genera, a greater percentage of egg hatching, heavier pupal weight and a higher percentage of fliers were found in the Qfly reared on the gel diet. Mating propensity and survival under nutritional stress was similar for adult Qfly that had been reared on the two larval diets. Overall, our findings demonstrate that the artificial larval diet strongly influences the microbiome and quality control measures of Qfly, with likely downstream effects on performance of flies released in SIT programs.